Pursuing Listeners’ Perceptual Response in Audio-Visual Interactions – Headphones vs Loudspeakers: A Case Study - MRÓZ, Bartłomiej; KOSTEK, Bożena (Archives of Acoustics, 2022)
This study investigates listeners’ perceptual responses in audio-visual interactions concerning binaural spatial audio. Audio stimuli are coupled with or without visual cues to the listeners. The subjective test participants are tasked to indicate the direction of the incoming sound while listening to the audio stimulus via loudspeakers or headphones with the head-related transfer function (HRTF) plugin. First, the methodology assumptions and the experimental setup are described to the participants. Then, the results are presented and analysed using statistical methods. The results indicate that the headphone trials showed much higher perceptual ambiguity for the listeners than when the sound is delivered via loudspeakers. The influence of the visual modality dominates the audio-visual evaluation when loudspeaker playback is employed. Moreover, when the visual stimulus is present, the headphone playback pattern of behavior is not always in response to the loudspeaker playback.